Annexin A1 attenuates microvascular complications through restoration of Akt signalling in a murine model of type 1 diabetes - Purvis, G; Chiazza, F; Chen, J; Azevedo-Loiola, R; Martin, L; Kusters, D; Reutelingsperger, C; Fountoulakis, N; Gnudi, L; Yaqoob, M; Collino, M; Thiemermann, C; et al. (Springer Verlag, 2017)
Aims/hypothesis: Microvascular complications in the heart and kidney are strongly associated with an overall rise in inflammation. Annexin A1 (ANXA1) is an endogenous anti-inflammatory molecule that limits and resolves inflammation. In this study, we have used a bedside to bench approach to investigate: (1) ANXA1 levels in individuals with type 1 diabetes; (2) the role of endogenous ANXA1 in nephropathy and cardiomyopathy in experimental type 1 diabetes; and (3) whether treatment with human recombinant ANXA1 attenuates nephropathy and cardiomyopathy in a murine model of type 1 diabetes. Methods: ANXA1 was measured in plasma from individuals with type 1 diabetes with or without nephropathy and healthy donors. Experimental type 1 diabetes was induced in mice by injection of streptozotocin (STZ; 45 mg/kg i.v. per day for 5 consecutive days) in C57BL/6 or Anxa1 −/− mice. Diabetic mice were treated with human recombinant (hr)ANXA1 (1 μg, 100 μl, 50 mmol/l HEPES; 140 mmol/l NaCl; pH 7.4, i.p.) or vehicle (100 μl, 50 mmol/l HEPES; 140 mmol/l NaCl; pH 7.4, i.p.). Results: Plasma levels of ANXA1 were elevated in individuals with type 1 diabetes with/without nephropathy compared with healthy individuals (66.0 ± 4.2/64.0 ± 4 ng/ml vs 35.9 ± 2.3 ng/ml; p < 0.05). Compared with diabetic wild-type (WT) mice, diabetic Anxa1 −/− mice exhibited a worse diabetic phenotype and developed more severe cardiac (ejection fraction; 76.1 ± 1.6% vs 49.9 ± 0.9%) and renal dysfunction (proteinuria; 89.3 ± 5.0 μg/mg vs 113.3 ± 5.5 μg/mg). Mechanistically, compared with non-diabetic WT mice, the degree of the phosphorylation of mitogen-activated protein kinases (MAPKs) p38, c-Jun N-terminal kinase (JNK) and extracellular signal-regulated kinase (ERK) was significantly higher in non-diabetic Anxa1 −/− mice in both the heart and kidney, and was further enhanced after STZ-induced type 1 diabetes. Prophylactic treatment with hrANXA1 (weeks 1–13) attenuated both cardiac (ejection fraction; 54.0 ± 1.6% vs 72.4 ± 1.0%) and renal (proteinuria; 89.3 ± 5.0 μg/mg vs 53.1 ± 3.4 μg/mg) dysfunction associated with STZ-induced diabetes, while therapeutic administration of hrANXA1 (weeks 8–13), after significant cardiac and renal dysfunction had already developed, halted the further functional decline in cardiac and renal function seen in diabetic mice administered vehicle. In addition, administration of hrANXA1 attenuated the increase in phosphorylation of p38, JNK and ERK, and restored phosphorylation of Akt in diabetic mice. Conclusions/interpretation: Overall, these results demonstrate that ANXA1 plasma levels are elevated in individuals with type 1 diabetes independent of a significant impairment in renal function. Furthermore, in mouse models with STZ-induced type 1 diabetes, ANXA1 protects against cardiac and renal dysfunction by returning MAPK signalling to baseline and activating pro-survival pathways (Akt). We propose ANXA1 to be a potential therapeutic option for the control of comorbidities in type 1 diabetes.